2016
DOI: 10.1159/000448123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preoperative Nutritional Status on Surgical Site Infection in Colorectal Cancer Resection

Abstract: Background/Aims: Postoperative complications of colorectal cancer (CRC) can sometimes be life threatening. Prevention of morbidity is therefore the most important issue, and among such complications, surgical site infections (SSIs) are the most critical. Predictive factors for SSI were evaluated. Patients and Methods: This was a retrospective study of 432 patients with CRC. SSIs were classified into incisional SSIs (iSSIs) and organ/space SSIs (o/sSSIs). Results: Preoperative serum albumin (relative risk (RR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Several studies have suggested that preoperative nutritional status is an independent risk factor for anastomotic leakage and wound infection in patients with CRC 44,45 . Our study also showed that GNRI was a significant risk factor for wound infection, but it was not a risk factor for anastomotic leakage.…”
Section: Variablesmentioning
confidence: 99%
“…Several studies have suggested that preoperative nutritional status is an independent risk factor for anastomotic leakage and wound infection in patients with CRC 44,45 . Our study also showed that GNRI was a significant risk factor for wound infection, but it was not a risk factor for anastomotic leakage.…”
Section: Variablesmentioning
confidence: 99%
“…Preoperative nutritional status is a risk factor for SSIs in colorectal cancer, and its proper preoperative management may reduce the risk of SSIs. [25]. Thus, the preoperative active supplementation of nutrition to maintain an appropriate level of serum A/G plays a signi cant bene cial role in the decrease of SSIs and other postoperative complications [26].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative nutritional status is a risk factor for SSIs in colorectal cancer, and its proper preoperative management may reduce the risk of SSIs. [25]. Thus, the preoperative active supplementation of nutrition to maintain an appropriate level of serum A/G plays a signi cant bene cial role in the decrease of SSIs and other postoperative complications [26].…”
Section: Days) After Adjusting For Confounding Variables Open Fractmentioning
confidence: 99%